The Epidermal Growth Factor Ligand Spitz Modulates Macrophage Efferocytosis, Wound Responses and Migration Dynamics During Drosophila Embryogenesis - Tardy, Olivier R.; Armitage, Emma L.; Prince, Lynne R.; Evans, Iwan R. (Frontiers in Cell and Developmental Biology, 2021)
How multifunctional cells such as macrophages interpret the different cues within their environment and undertake an appropriate response is a key question in developmental biology. Understanding how cues are prioritised is critical to answering this – both the clearance of apoptotic cells (efferocytosis) and the migration towards damaged tissue is dependent on macrophages being able to interpret and prioritise multiple chemoattractants, polarise, and then undertake an appropriate migratory response. Here, we investigate the role of Spitz, the cardinal Drosophila epidermal growth factor (EGF) ligand, in regulation of macrophage behaviour in the developing fly embryo, using activated variants with differential diffusion properties. Our results show that misexpression of activated Spitz can impact macrophage polarity and lead to clustering of cells in a variant-specific manner, when expressed either in macrophages or the developing fly heart. Spitz can also alter macrophage distribution and perturb apoptotic cell clearance undertaken by these phagocytic cells without affecting the overall levels of apoptosis within the embryo. Expression of active Spitz, but not a membrane-bound variant, can also increase macrophage migration speeds and impair their inflammatory responses to injury. The fact that the presence of Spitz specifically undermines the recruitment of more distal cells to wound sites suggests that Spitz desensitises macrophages to wounds or is able to compete for their attention where wound signals are weaker. Taken together these results suggest this molecule regulates macrophage migration and their ability to dispose of apoptotic cells. This work identifies a novel regulator of Drosophila macrophage function and provides insights into signal prioritisation and integration in vivo. Given the importance of apoptotic cell clearance and inflammation in human disease, this work may help us to understand the role EGF ligands play in immune cell recruitment during development and at sites of disease pathology.